In Silico Larvicidal Activity Study of Six Limonoids Against Mosquito Larvae (Aedes aegypti L.) Ecdysone Receptor Protein - Rajab, Mohamed Said (Sciences of Phytochemistry, 2024)
In an earlier study, six limonoids namely pyroangolensolide, calodendrolide, limonin, limonin diosphenol, harrisonin and pedonin were reported to exhibit varying larvicidal activity against Aedes aegypti L. second instar larvae. The degraded limonoids exhibited a higher larvicidal activity relative to the more complex compounds. To investigate this observation at the relevant Aedes aegypti L. receptor level, the six limonoids were subjected to an in silico docking study to evaluate the binding characteristics of the selected limonoids in the ecdysone receptor (EcR) protein (PDB code 1z5x). This was compared with the binding affinity of the dipteran specific ecdysone agonist, RH 5849 (1,2-Dibenzoyl-1-tert-butylhydrazine). The EcR protein1z5x-LBP was identified from literature data. The binding energies of the ligands docked in the EcR protein 1z5x-LBP ranged from 3.0 to -9.1 kcal/mol and the dissociation constants (Kd) ranged from 2.10×10-7 M to 1.59×10+2 M. RH 5849 had a binding energy of -8.9 kcal/mol which was comparable with those displayed by pyroangolensolide (-9.1 kcal/mol) and calodendrolide (-9.0 kcal mol). Two pharmacophoric factors were important in the observed binding: (a) the hydrogen-bonding interactions by the residues Arg 271, Arg 275 Tyr 296. Thr231 and Ala 286 and (b) the hydrophobic pocket residues Met 268, Met 272, Met 269, Phe 285, and Leu 308. The binding affinities of the selected limonoids in the EcR pocket compared well with the observed larvicidal activity as reported earlier and in the literature. This study offers an opportunity to develop structurally simpler and specific receptor targeted larvicides against Aedes aegypti L.